Analysis of curved optical absolute visual fates of super colony of Type II (SN II) (Baghdad Science Journal, 2006)
Were analyzed curved optical fates Almarchih absolute colony of the binary type, the Great Palmstqrh using mathematical relationships derived for that and that gave us the results closer to the results of the observed spectral Great Colonial